Identification of serum immunoglobulin M (IgM) of crucian carp (Carassius auratus gibelio) and immune response to cyprinid herpesvirus 2 infection - Shuran Wang; Haotian Wu; Longlong Wang; Pinhua Wang; Liqun Lu; Yousheng Jiang; Ye Zhang; Dan Xu (Aquaculture and Fisheries, 2024)
Crucian carp (Carassius auratus gibelio), an extensively cultivated freshwater fish, was one of the model species for the study of fish immunology. Polyclonal antibodies were advantageous molecular tools for studying teleost immune system. Specifically, polyclonal antibodies reacting with immunoglobulins (Ig) were used successfully in studies of the teleost fishes. In the present study, we produced polyclonal antibody against CH2 domains of crucian carp IgM, and measured the in vivo dynamics of IgM mRNA caused by CyHV-2 infection. The recombinant protein IgM with relative molecular weight about 53 KD was correctly expressed in prokaryotic cells. The specificity of the polyclonal antibody was evaluated by Western blotting and results revealed that the antibody not only specifically recognized crucian carp serum but also cross-reacted with grass carp serum. Quantitative RT-PCR analysis demonstrated the expression of IgM mRNA changed significantly after CyHV-2 infection. The expression of IgM in the kidney increased and reached a maximum at 6 h post-infection (hpi), while dropped to a low level at 5 days post-infection (dpi). In conclusion, the expression of IgM was significantly upregulated in the kidney of crucian carp infected with CyHV-2, indicating that IgM played a potential role in systemic immunity against viral infection. Polyclonal antibody against crucian carp IgM had certain clinical relevance, which might provide insight into the early stage of virus infection and prevention of the disease.